Stimulation, Detection, Early Intervention of Growth and Development: A Case Study of a Child with Speech Delay - Ulfah, Mega; Dewi, Mustika; Qonita, Jihan (STIKes Patria Husada Blitar, 2024)
Speech delay is a condition where a child's speech and language development are significantly below the milestones of other children at the same age. The delay in school aged children will impact the child's enrollment in school. The purpose of this study was to describe stimulation, detection, and intervention in children with speech delay. The research used a qualitative approach with a case study design. The research population consisted of 97 children with speech delay. The inclusion criteria were children aged 2-3 years old, willingness to participate as respondents and presence during the research. The exclusion criteria were children with hearing loss, autism, attention deficit hyperactivity disorder (ADHD) and chromosome abnormalities. The sample was chosen by using purposive sampling technique. The subject was a child aged 32 months old. The data was collected through interviews, observation, and documentation. Based on the results of the study, it can be concluded that the child is classified as a functional speech delay caused by lack of stimulation. The child was first identified by parents having speech problems at the age of 18 months. Intervention was done through speech therapy. It is recommended that parents can stimulate and monitor children's development especially at the age of 0-2 years to avoid developmental problems, especially speech delay